Etiological Profile of Neonatal Seizures and Prognostic Factors for Adverse Outcome: A Single Center Prospective Study - Singh, Srijana Dongol; Bahadur Shrestha, Ranendra Prakash; Shrestha, Asim (Journal of Lumbini Medical College, 2018)
Introduction: Neonatal seizure is the most common manifestation and an important determinant of outcome of neurological disorders in newborn period. This study aims to delineate the etiological profile and neurodevelopmental outcome of neonatal seizures and also to identify predictors for adverse outcome.Methods: One hundred and seventeen neonates with clinically proven seizures admitted in Dhulikhel Hospital from February 2014 to February 2016 were recruited. All of them underwent necessary neurological diagnostic tests. The survivors were followed up for at least three times within the first 18 months of life. Prognostic value of factors for adverse outcomes were analyzed with Chi square test and binary logistic regression analysis.Results: Among a total of 954 neonates admitted, 117 (12.26%) developed clinical seizures. The most common cause of neonatal seizure was hypoxic ischemic encephalopathy (n=69, 59%), followed by infection (n=20, 17.09%), and metabolic disturbances (n=16, 13.7%). The outcomes were mortality (n=16, 13.7%), post neonatal seizure (n=18, 15.4%), developmental delay (n=31, 26.5%), vision impairment (n=19, 16.2%) and hearing impairment (n=26, 22.2%). Low Apgar scores at one minute (p=0.03) and five minutes (p=0.001), early onset seizure (p